(untitled) (Journal of Nepal Geological Society, 2018)
Glacial Lake Outburst Flood (GLOF) is one of the potential disaster of Nepal. The Imja glacial lake is considered as one of the fastest growing glacial lake with high risk of GLOF. The internal structure of moraine dams, especially the distribution of buried ice blocks and permafrost materials is key factors in assessing GLOF risk. This study covers exploration and assessment of subsurface conditions of the moraine material such as quantification of buried ice, seepage channel and permafrost material distribution. The geophysical study of dam was carried out by using Dipole–dipole array of Electrical Resistivity Tomography (ERT) method. This study presents the results regarding use of electrical resistivity survey for assessment of the subsurface buried glacier ice and permafrost zones within the dam of the Imja glacial lake. The interpretation of resistivity data at end moraine of Imja glacial lake is based not only on specific resistivity values, but also with field observations and correlation with previous studies. The maximum depth of information obtained from the modeling is about 25 m and; highest and lowest values of resistivity ranges from 117 Wm to 2682240 Wm. The distribution of major subsurface materials from lowest resistivity value to highest resistivity values are classified as saturated moraine (<5000 Wm), frozen moraine (5000 Wm to 20000 Wm) and dead ice (>20000 Wm). The distribution of dead buried ice in moraine dam is found to be heterogeneous. The minimum and maximum depth of dead ice from surface is about 0 m to 20 m at various locations. Based on the information of this study, an open channel was cut through the lake to lower its level and the result is found to be successful.